2019
DOI: 10.1055/s-0039-1695720
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Imaging in Osteoarthritis

Abstract: Osteoarthritis (OA) is the most common joint disease in the United States. The prevalence of OA is rising due to an aging population and increasing rates of obesity. Magnetic resonance imaging (MRI) allows an incomparable noninvasive assessment of all joint structures. Irreversible and progressive degradation of the articular cartilage remains the hallmark feature of OA. To date, attempts at developing disease-modifying drugs or biomechanical interventions for treating OA have proven unsuccessful. MRI-based ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 94 publications
0
14
0
1
Order By: Relevance
“…Some scholars have studied the correlation between the degree of cartilage injury and knee joint pain, sti ness, and function WOMAC scores and found that the WOMAC scores of pain and function between di erent cartilage injury grades were statistically signi cant, while the WOMAC score of sti ness was not statistically signi cant [30]. ere was no signi cant di erence in WOMAC scores between the mild cartilage injury or normal group and the severe cartilage injury group [31].…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have studied the correlation between the degree of cartilage injury and knee joint pain, sti ness, and function WOMAC scores and found that the WOMAC scores of pain and function between di erent cartilage injury grades were statistically signi cant, while the WOMAC score of sti ness was not statistically signi cant [30]. ere was no signi cant di erence in WOMAC scores between the mild cartilage injury or normal group and the severe cartilage injury group [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, we choose the MRI of Recht grade as a result of it being able to assess soft tissue and KOA affects in the articular cartilage 28 , 29 . The primary approach currently available for KOA diagnosis is MRI, which aids in diagnosing KOA, determining KOA progression and prognosis, and monitoring treatment responses 30 . Using radiography alone to measure the loss of cartilage has limited clinical utility and only a modest correlation with symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…However, we choose the MRI of Recht grade as a result of it can assess soft tissue preferably and KOA affects the articular cartilage particularly [28,29] . The primary approaches currently available for KOA diagnosis are magnetic resonance imaging (MRI) which aids in diagnosing KOA, determining KOA progression and prognosis, and monitoring treatment responses [30] . Using radiography alone to measure the loss of cartilage has limited clinical utility and only a modest correlation with symptom severity.…”
Section: Discussionmentioning
confidence: 99%